Piping and pipeline assessment guide - Escoe, A. Keith (Stationary equipment assessment series ;, 2006)
Whether its called fixed equipment (at ExxonMobil), stationary equipment (at Shell), or static equipment (in Europe), this type of equipment is the bread and butter of any process plant. Used in the petrochemical industry, pharmaceutical industry, food processing industry, paper industry, and the manufacturing process industries, stationary equipment must be kept operational and reliable for companies to maintain production and for employees to be safe from accidents. This series, the most comprehensive of its kind, uses real-life examples and time-tested rules of thumb to guide the mechanical engineer through issues of reliability and fitness-for-service. This volume on piping and pipeline assessment is the only handbook that the mechanical or pipeline engineer needs to assess pipes and pipelines for reliability and fitness-for-service. * Provides essential insight to make informed decisions on when to run, alter, repair, monitor, or replace equipment * How to perform these type of assessments and calculations on pipelines is a hot' issue in the petrochemical industry at this time * There is very little information on the market right now for pipers and pipeliners with regard to pipe and pipeline fitness-for-service.